Children's Literature and Imaginative Geography - Hudson, Aïda, 1951- (Book collections on Project MUSE., 2019)
Where do children travel when they read a story? In this collection, scholars and authors explore the imaginative geography of a wide range of places, from those of Indigenous myth to the fantasy worlds of Middle-earth, Earthsea, or Pacificus, from the semi-fantastic Wild Wood to real-world places like Canada's North, Chicago's World Fair, or the modern urban garden. What happens to young protagonists who explore new worlds, whether fantastic or realistic? What happens when Old World and New World myths collide? How do Indigenous myth and sense of place figure in books for the young? How do environmental or post-colonial concerns, history, memory, or even the unconscious affect an author's creation of place? How are steampunk and science fiction mythically re-enchanting for children? Imaginative geography means imaged earth writing: it creates what readers see when they enter the world of fiction. Exploring diverse genres for children, including picture books, fantasy, steampunk, and realistic novels as well as plays from Canada, the United States, the United Kingdom, and Ireland from the early nineteenth century to the present, Children's Literature and Imaginative Geography provides new geographical perspectives on children's literature.